Effect of oleic acid modified polymeric bilayered nanoparticles on percutaneous delivery of spantide II and ketoprofen - Shah, Punit (2011)
The objective of present study was to evaluate the effect of oleic acid modified polymeric bilayered nanoparticles (NPS) on combined delivery of two anti-inflammatory drugs, spantide II (SP) and ketoprofen (KP) on the skin permeation. NPS were prepared using poly(lactic-co-glycolic acid) (PLGA) and chitosan. SP and KP were encapsulated in different layers alone or/and in combination (KP-NPS, SP-NPS and SP+KP-NPS). The surface of NPS was modified with oleic acid (OA) (`Nanoease' technology) using an established procedure in the laboratory (KP-NPS-OA, SP-NPS-OA and SP+KP-NPS-OA). Fluorescent dyes (DiO and DID) containing surface modified (DiO-NPS-OA and DID-NPS-OA) and unmodified NPS (DiO-NPS and DID-NPS) were visualized in lateral rat skin sections using confocal microscopy and Raman confocal spectroscopy after skin permeation. In vitro skin permeation was performed in dermatomed human skin and HPLC was used to analyze the drug levels in different skin layers. Further, allergic contact dermatitis (ACD) model was used to evaluate the response of KP-NPS, SP-NPS, SP+KP-NPS, KP-NPS-OA, SP-NPS-OA and SP+KP-NPS-OA treatment in C57BL/6 mice. The fluorescence from OA modified NPS was observed upto depth of 240 μm and was significantly higher as compared to non-modified NPS. The amount of SP and KP retained in skin layers from OA modified NPS increased by several folds compare to unmodified NPS and control solution. In addition, the combination index value calculated from ACD response for solution suggested additive effect and moderate synergism for NPS-OA. Our results strongly suggest that surface modification of bilayered nanoparticles with oleic acid improved drug delivery to the deeper skin layers.